Grape Phytochemicals and Vitamin D in the Alleviation of Lung Disorders - Santa, Kazuki (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Typical lung diseases are pneumonia, asthma, sleep apnea syndrome (SA), interstitial pneumonia (IP), lung cancer, and chronic obstructive pulmonary disease (COPD). Coronavirus disease 2019 (COVID-19) is a type of viral pneumonia. Many researchers have reported that phytochemicals (chemical compounds produced by plants) and vitamin D are useful in stimulating our immunity. This review discusses the alleviation of lung diseases by grape phytochemicals and vitamin D. Discussion: Pneumonia is an acute inflammation caused by the infection of pathogens; the worst case is a fatal cytokine storm in the lung. In asthma, allergens, tobacco smoke, or air pollution may cause seizures. Lung diseases caused by lung fibrosis may manifest chronic inflammation, progress into alveolar fibrosis, and cause respiratory malfunction. SA is a lifestyle disease related to obesity and metabolic syndrome. To alleviate these symptoms, changing the eating habit is one of the strategies. Improvement in the daily lifestyle reduces the risk of lung cancer. Self-management, including nutritional management and exercise, is very important for COPD patients in addition to pharmacotherapy. Conclusion: The intake of grape phytochemicals and vitamin D prevents the progress of lung diseases. Both phytochemicals and vitamin D prevent the production of proinflammatory cytokine, TNF-α, that is responsible for inflammation and lung diseases. Daily intake of grape phytochemicals is important. The optimum vitamin D level in serum is > 30 ng/mL. For the prevention of lung diseases, upregulating immunity and maintaining good gut microbiota are important because gut microbiota change depending on what we eat.
Keywords: interstitial pneumonia (IP)